Hypoxic/Ischemic Inflammation, MicroRNAs and δ-Opioid Receptors: Hypoxia/Ischemia-Sensitive Versus-Insensitive Organs - Chen, Yimeng; He, Yichen; Zhao, Shuchen; He, Xiaozhou; Xue, Dong; Xia, Ying (Frontiers in Aging Neuroscience, 2022)
Hypoxia and ischemia cause inflammatory injury and critically participate in the pathogenesis of various diseases in various organs. However, the protective strategies against hypoxic and ischemic insults are very limited in clinical settings up to date. It is of utmost importance to improve our understanding of hypoxic/ischemic (H/I) inflammation and find novel therapies for better prevention/treatment of H/I injury. Recent studies provide strong evidence that the expression of microRNAs (miRNAs), which regulate gene expression and affect H/I inflammation through post-transcriptional mechanisms, are differentially altered in response to H/I stress, while δ-opioid receptors (DOR) play a protective role against H/I insults in different organs, including both H/I-sensitive organs (e.g., brain, kidney and heart) and H/I-insensitive organs (e.g., liver and muscle). Indeed, many studies have demonstrated the crucial role of the DOR-mediated cyto-protection against H/I injury by several molecular pathways, including NLRP3 inflammasome modulated by miRNAs. In this review, we summarize our recent studies along with those of others worldwide, and compare the effects of DOR on H/I expression of miRNAs in H/I-sensitive and -insensitive organs. The alternation in miRNA expression profiles upon DOR activation and the potential impact on inflammatory injury in different organs under normoxic and hypoxic conditions are discussed at molecular and cellular levels. More in-depth investigations into this field may provide novel clues for new protective strategies against H/I inflammation in different types of organs.